GEOSPATIAL ESTIMATION OF ROOFTOP SOLAR PHOTOVOLTAIC POTENTIAL IN CALABAR MUNICIPAL, CROSS RIVER STATE, NIGERIA - Ugbong, Paul U.; Isma’il, Muhammad; Usman, A. K. (FUDMA JOURNAL OF SCIENCES, 2023)
The availability of significant solar resource and the continuous hike in economic activities as well as an increased population in Calabar Municipal holds a substantial solar photovoltaic (PV) potential of rooftops in the city. This is as a result of the consequent increase in urban households. This Research work is aimed at estimating solar PV potential of rooftops in the study area using geospatial techniques. It adopted Geospatial techniques’ approach in identifying rooftops available for PV deployment in Calabar Municipal. High resolution satellite imagery gotten from google Earth, Digital surface model (DSM)/ Digital elevation model (DEM) and ArcGIS 10.8 were employed in this study. In other to estimate the PV potential of rooftops, criteria such as Solar Radiation/ Irradiance, Total Roof Area (Building footprints), Slope (rooftop inclination angle) and Aspect (Buildings’ orientation) were analyzed. The results gotten from these analyses were analyzed further and rooftops that fall below the acceptable range of the aforementioned criteria were excluded from the analysis. Results showed that the total roof area in Calabar Municipal was estimated as 5,965,916.44 m2 (5.97 km2) while the available roof area suitable for PV installations was evaluated as 5,964,966.42 m2 (5.96 km2). The findings of this research indicates that Calabar Municipal has good solar radiation as well as enough suitable rooftop area hence a very good place for solar PV deployments. Also, this study is accurate enough to be used as a guide in decision making on power (electricity) generation in Calabar Municipal of Cross River State.
Keywords: Rooftop Photovoltaic Potential; Solar Radiation; Calabar Municipal; Geospatial Techniques